2018
DOI: 10.3390/app8040516
|View full text |Cite
|
Sign up to set email alerts
|

A User-Centered Mobile Cloud Computing Platform for Improving Knowledge Management in Small-to-Medium Enterprises in the Chilean Construction Industry

Abstract: Knowledge management (KM) is a key element for the development of small-to-medium enterprises (SMEs) in the construction industry. This is particularly relevant in Chile, where this industry is composed almost entirely of SMEs. Although various KM system proposals can be found in the literature, they are not suitable for SMEs, due to usability problems, budget constraints, and time and connectivity issues. Mobile Cloud Computing (MCC) systems offer several advantages to construction SMEs, but they have not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 74 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…BIM is specifically useful during for monitoring cause it gives better understanding environmental conditions and also an effective process for design evaluation and construction (Habibi, 2017). Several studies also suggested that the usage of mobile technology can assist in capturing real time information on-site personnel in construction (Igwe et al, 2021;Núñez et al, 2018;Osunsanmi et al, 2020). Real time collaborative work amongst the project designer and other members can be executed regardless of the location and virtual meeting can also be hosted through cloud computing technology (Bello et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…BIM is specifically useful during for monitoring cause it gives better understanding environmental conditions and also an effective process for design evaluation and construction (Habibi, 2017). Several studies also suggested that the usage of mobile technology can assist in capturing real time information on-site personnel in construction (Igwe et al, 2021;Núñez et al, 2018;Osunsanmi et al, 2020). Real time collaborative work amongst the project designer and other members can be executed regardless of the location and virtual meeting can also be hosted through cloud computing technology (Bello et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Transforming corporate sustainability objectives and initiative strategies takes time and effort. According to Noteboom et al and Núñez et al, it is necessary to balance factors affecting society, the economy, and the environment and their overall sustainability in smart development [39,40]. The development of building industry sustainability has prompted a search for practical methods to incorporate this concept into existing work settings.…”
Section: Related Literaturementioning
confidence: 99%
“…In a construction project, KMP factors focus mainly on human experiences and their interrelationships that may be implemented differently depending on knowledge viewpoints [18,25]. For example, if the perspective on knowledge is an object that can be stored and manipulated, then KMP factors may concentrate on establishing and managing knowledge stocks [26]. On the other hand, if knowledge is considered to be people's awareness, then the primary KMP activities may focus on learning, sharing, and creating communication and interaction among people to enhance knowledge [27].…”
Section: Literature Review 21 Kmp Factors In the Construction Industrymentioning
confidence: 99%